Surface hardening alloy VT6 of electric explosion and by electron beam - Ivanov Yu. F. Yuriy Fedorovich; Kobzareva T. Yu.; Raikov S. V.; Gromov V. E.; Soskova N. A.; Budovskikh E. A. (2014, 2014)
Title screen